Applying the natural transform iterative technique for fractional high-dimension equations of acoustic waves - Zada, Laiq; Ali, Nasir; Nawaz, Rashid; Jamshed, Wasim; Eid, Mohamed R.; Tag El Din, El Sayed M.; Khalifa, Hamiden Abd El- Wahed; ElSeabee, Fayza Abdel Aziz (Frontiers in Energy Research, 2022)
In the present study, the natural transform iterative method (NTIM) has been implemented for the solution of a fractional Zakharavo–Kuznetsov (FZK) equation. NTIM is a relatively new technique for handling non-linear fractional differential equations. The method is tested upon the two non-linear FZK equalities. The solution of the proposed technique has been compared with the existing perturbation–iteration algorithm (PIA) method and residual power series method (RPSM). From the numerical results, it is clear that the method handles non-linear differential equations very suitably and provides the results in very closed accord with the accurate solution. As a result, the NTIM approach is regarded as one of the finest analytical techniques for solving fractional-order linear and non-linear problems.